2021
DOI: 10.1016/j.cegh.2021.100765
|View full text |Cite
|
Sign up to set email alerts
|

Study on knowledge of chemotherapy's adverse effects and their self-care ability to manage - The cancer survivors impact

Abstract: Introduction: Cancer is the second leading cause of death globally. Adverse effects of chemotherapy affect physiological and psychological aspects of human life. Self-care practice to manage side effects can improve the quality of life. Aims: The study investigates the relationship between knowledge on the adverse effects of chemotherapy and self-care ability to manage chemotherapy survivors' side effects. Subjects and methods: This was a single centre, Cross-sectional, descriptive study. A face-to-face interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 9 publications
3
28
0
Order By: Relevance
“…Therefore, TNBC has a low response to therapeutics and is highly invasive [ 5 , 6 ]. Although chemotherapy is regarded as one of the most effective cancer treatments, its adverse effects in such treatments include reduced immunity, decreased leukocyte count, and alopecia areata, which have been received with critical concern [ 7 ]. To avoid these adverse effects, curcumin, a well-known polyphenolic compound from the rhizome of Curcuma longa , which possesses anticancer activity against various types of cancers, has received considerable attention for development as a novel anticancer agent with fewer adverse effects [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TNBC has a low response to therapeutics and is highly invasive [ 5 , 6 ]. Although chemotherapy is regarded as one of the most effective cancer treatments, its adverse effects in such treatments include reduced immunity, decreased leukocyte count, and alopecia areata, which have been received with critical concern [ 7 ]. To avoid these adverse effects, curcumin, a well-known polyphenolic compound from the rhizome of Curcuma longa , which possesses anticancer activity against various types of cancers, has received considerable attention for development as a novel anticancer agent with fewer adverse effects [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, advancements have been achieved in the prevention and therapeutic approaches, resulting in longer lifetimes or even cures for certain patients with cancer. Unfortunately, chemotherapy and radiotherapy, the two gold stones in cancer treatment, are also painful for patients and cause severe side effects [ 2 ]. Therefore, developing innovative anti-cancer therapies with less side effects needs a comprehensive understanding of cancer biology.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 A recent study also indicated that having adequate knowledge of chemotherapy treatment enhanced patients’ self-care practice to manage side effects. 10 …”
Section: Introductionmentioning
confidence: 99%